Efektivitas Bahan Ajar E-Book Berbasis Android Menggunakan Metode Scaffolding Pada Mata Pelajaran Ekonomi di MA Negeri Bangkalan - Widya, Riska Nur; Susanti; Surjanti, Jun (Universitas Pendidikan Ganesha, 2022)
In the current era of revolution 4.0, the demands for renewal in the field of education are getting higher. As in the current post-pandemic period, the need for more practical and effective teaching materials is needed, balanced with the use of learning methods that are able to provide convenience and adapt to student learning styles. such as the use of teaching materials in the form of electronic books (E-books) which are packaged in the form of android-based learning media. Where the E-Book here also applies the scaffolding method as a form of assistance in the form of clues or instructions related to material that is quite difficult to understand. the type of research carried out is R&D (Research & Development) by adapting the development model of Thiagarajan, Semmel & Semmel (1974). The results of the study obtained a feasibility level of 85.6% with the criteria of